The Evaluation of the Use of Container Houses in Meeting Housing Needs Based on a Survey of Real Estate Agents - Bartkowiak, Piotr; Strączkowski, Łukasz (Journal of Public Governance, 2024)
Objectives: The problem of housing needs requires continuous monitoring as well as analysis and evaluation of its solutions. One such solution could be container housing, positive examples of which can be found abroad, e.g. in Sweden or Canada. For this to happen, an attempt should be made to assess whether this type of construction has a chance to appear in Poland and whether it can be an attractive segment from the point of view of the market and meeting the needs of buyers. Therefore, the objectives of the study were to assess: (1) whether container housing can become a segment seriously considered in the context of meeting housing needs in Poland; (2) the interest of potential buyers of housing in container housing; (3) the attractiveness of container housing. Research Design & Methods: To achieve the objectives, a survey was conducted in Q4 2023 among 67 real estate agents as entities that serve clients on a daily basis and know their needs and preferences. Implications / Recommendations: The obtained results indicate that it is currently difficult to say unequivocally whether container housing can become a segment seriously considered for meeting housing needs in Poland. On the one hand, the results show that there are serious doubts about this (small number of offers, low customer interest, little knowledge of the subject, customer fears), while on the other hand, container flats can be visually attractive to customers, are full-featured, and, most importantly, are definitely cheaper than those built with traditional technology. These could be the factors for the potential success of this market segment, perhaps even on such a scale that more mass production of this type of housing would become the so-called ‘game changer’ of the market. Contribution / Value Added: It is necessary to increase people’s awareness, promote this type of construction (including showing positive examples from abroad), and reduce fears and doubts about living in container buildings. Article classification: research article JEL classification: O18, R21, R33